The Changes in the Meaning of the Word 'Azab' In Social Media Status - Mutmainnah, Yulia; Hardiyanti, Diana (Dinamika Bahasa dan Budaya, 2024)
As social life develops, the language used by the language community also experiences development and change. The word azab, widely used in communication, has changed its meaning. This research is semantic research, especially on changes in the meaning of words, which aims to get a clear picture of the changes in the meaning of the word azab, which is used in statuses on social media Facebook, Twitter, and Instagram. These three social media were chosen because they are the three big social media that people use to update their status in phrases and sentences containing the word azab. This research uses a qualitative descriptive method to describe linguistic phenomena in society. By using a phenomenological approach, in this research, it was found that the word azab was by its true meaning, but some meanings expanded and shifted. Keywords: azab, meaning, expended meaning, sifted meaning